ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN TERHADAP PENGELOLAAN LIMBAH RUMAH SAKIT DI KOTA JAYAPURA - Oeghoede, Christy J. A.; Rofingatun, Siti; Larasati, Rudiawie (Jurnal Akuntansi, Audit, dan Aset, 2020)
This study aims to examine the application of environmental accounting to waste management inhospitals in the city of Jayapura. This study used a survey in the form of a questionnaire to hospitalemployee respondents. The population in this study amounted to 70 people spread across fourhospitals including Jayapura Hospital, Abepura Hospital, Bhayangkara Hospital, and DianHarapan Hospital. The sampling technique in this study using purposive sampling in order toobtain the results of 50 people/respondents. The data analysis in this research used a validity test,reliability test, and structural model with the WarpPLS 7.0 program.The results of this study indicate that (1) the environmental responsibility variable has a positiveand significant effect on hospital waste management, and (2) the monetary environmentalaccounting variable has a positive and insignificant effect on hospital waste management.